O04.1 Novel pathway to ceftriaxone resistance in clinical isolates of N. gonorrhoeae via point mutations in the RNA polymerase. (14th July 2019) - Palace, Samantha; Wang, Yi; Rubin, Daniel; Grad, Yonatan
Abstract : Background: Widespread antimicrobial resistance in Neisseria gonorrhoeae has limited the effective treatment options. Cephalosporins remain one of the few classes of antibiotics recommended for gonococcal infections, but reduced susceptibility to the third-generation cephalosporins, including ceftriaxone, has emerged. Most reduced susceptibility to ceftriaxone is caused by an alternative penA (PBP2) allele. However, the isolates with the among the highest level cephalosporin resistance identified in the US lack this allele and other penA resistance mutations, raising the possibility of cephalosporin resistance not mediated directly through penA. Methods: To identify the genetic basis of resistance in these isolates, we employed an undirected transformation strategy, and used molecular microbiology and genetics methods to investigate the mechanism of resistance. Results: Here, we show that resistance to ESCs has arisen in clinical isolates multiple times through distinct mutations in the RNA polymerase components rpoB and rpoD. The resistance caused by these changes is not a general tolerance response: these mutations neither changed the growth rate in vitro nor altered susceptibility to other classes of antibiotics (including penicillin). These mutations result in large variations in transcription, including in genes coding for penicillin binding proteins (increase in PBP1, decrease in PBPs 3 and 4) and pilus pore. We show that increases in PBP1 protein levels contribute to the rise in CRO MIC, likely through replacement of inhibited PBP2 activity, though other factors are needed to recapitulate the resistance seen in the clinical isolates with rpoB and rpoD mutations. Conclusion: Pathways to extended spectrum cephalosporin resistance do not require alterations to penA (PBP2) and can arise through mutations in components of the RNA polymerase holoenzyme. Additional pathways to cephalosporin resistance in goncooccus remain to be identified. These findings have implications for the development of molecular diagnostics and for understanding the mechanistic basis of cephalosporin resistance. Disclosure: No significant relationships.